The genetic puzzle of multicopy genes: challenges and troubleshooting - Vania Gabriela Sedano Partida; Henrique Moura Dias; Maria Teresa Portes; Marie-Anne Van Sluys (Plant Methods)
Abstract Background Studies of multicopy genes impose challenges related to gene redundancy and sequence similarity among copies. However, recent advances in molecular biology and genomics tools associated with dedicated databases facilitate their study. Thus, the present work emphasizes the need for rigorous methodologies and standardized approaches to interpret RT-qPCR results accurately. Results Data from Physcomitrium patens provides a comprehensive five-step protocol, using thiamine thiazole synthase (THI1) and sucrose 6-phosphate phosphohydrolase (S6PP) genes as proof of concept to showcase a systematic workflow for studying multicopy genes. Beyond examining genes of interest, we highlight the critical role of choosing appropriate internal controls in the analytical process for interpreting gene expression patterns accurately. We emphasize the importance of identifying the relevant orthologous gene, recognizing the inherent challenges in determining the most functional copy for subsequent studies. Our objective is to enhance comprehension of gene redundancy by dissecting multicopy genes' genomic landscape and its characteristics. Furthermore, we address the decision-making process surrounding the expression level quantification of multicopy genes. Conclusions The study of multicopy genes discloses early events for functional adaptation. Here, we discuss the significance of multicopy genes in plant biology and provide an experimental protocol to analyze them. As plant systems are strongly influenced by light/dark cycles, challenges inherent to circadian processes are also acknowledged. Therefore, our comprehensive approach aims to advance the understanding of multicopy gene dynamics, offering practical methodologies and contributing with valuable insights to the scientific community.